SIFAT PAPAN PARTIKEL DARI SERAT TANDAN KOSONG SAWIT DAN SERBUK KAYU DENGAN PEREKAT UREA FORMALDEHIDA (The Properties of Particle Board from Oil Palm Empty Fruit Bunches Fiber Sawdust with Urea Formaldehyde Resin) - Djoko Purwanto (Kementerian Perindustrian, 2016)
A palm oil mill with a capacity of hundred thousand tons of fresh fruit bunches per year will produce palm fiber waste about 12,000 tons. Recently, the use of palm empty fruit bunches (OPEFB) fiber is as fuel for electricity generation in the industry. Palm fiber waste contains lignocellulose materials as a feedstock to particle board manufacture. The aim of this research is to evaluate the properties of particle board from a mixture of OPEFB fiber and sawdust. The ratio of OPEFB fiber and sawdust are 100% : 0%; 75% : 25%; 50% : 50%; 25% : 75% and 0% : 100%, plus urea formaldehyde adhesive in a concentration of 11%. The boards were pressed using a clamp pressure of 16 kg/cm2 for 15 minutes at a temperature of 110 – 120 0C. The testing methods and standards of physical properties (moisture contents, thickness swelling, density) and mechanical (modulus of elasticity/MOE, modulus of rupture/MOR, screw withdrawal and internal bond strengths) refers to the SNI. 03 – 2105 - 2006. The results showed that the particle board made from 100% OPEFB fiber produces modulus of elasticity/MOE 1594.88 kg/cm2; modulus of rupture/MOR 18.08 kg/cm2; screw withdrawal 31.34 kg/cm2 and internal bond strength 0.86 kg/cm2. The addition of sawdust for 50% can improve modulus of elasticity/MOE, modulus of rupture/MOR and internal bond strength.